Trickster as personification of praxis - Carvalho, Silvia Maria Schmuziger de (Universidade Estadual Paulista / UNESP, 2009)
This article tries to establish a correlalion between necessities of cynegethic way of life (or "punching economy") respecting perception of "negative feed-back", "feed-back", practices toward nature, and the idealization of trickster-figure.